Treatment methods for sugar rich wastewater: A review - Sadia Fida; Maria Yasmeen; Rabia Adnan; Muhammad Zeeshan (Cleaner Water)
Sugarcane has been recognized as a cash crop in both developed and developing countries for the past century. The sugar manufacturing process requires large volumes of water and consequently generates high-strength wastewater, which, if not treated properly, poses significant environmental risks. This review paper focuses on various treatment techniques for sugar industry effluents including physicochemical, aerobic, anaerobic, and membrane-based approaches. While aerobic and membrane-based methods yield promising results, they are not cost-effective due to high energy demands and challenges related to sludge disposal. Anaerobic methods are more energy-efficient, enabling energy recovery as methane and hydrogen gas while producing less sludge. Sugar industry effluents, which have high organic concentrations, offer great potential for energy recovery through anaerobic treatment. However, the application of anaerobic methods on a commercial scale is limited by long startup periods and seasonal variations in effluent characteristics. The combination of high-rate anaerobic and aerobic methods has proven effective for treating high-strength wastewater.